The culture map : decoding how people think, lead, and get things done across cultures - Meyer, Erin, 1971- (PublicAffairs, 2015)
Práce přibližuje různá specifika jednotlivých kultur z celého světa, jejichž opomenutí může mít katastrofální následky pro zdárné dosažení obchodní dohody.
Keywords: interkulturní komunikace; diversity management; interkulturní psychologie; interkulturní management; intercultural communication; diversity in the workplace; cross-cultural psychology; intercultural management; populárně-naučné publikace; popular works